RESPON TIGA VARIETAS JAGUNG PULUT TERHADAP PENAMBAHAN DOSIS PEMUPUKAN UREA - Edy, Edy; Haris, Abdul (Percetakan Umi Toaha Makassar, 2025)
Waxy corn (Zea mays L. var. ceratina) is one type of corn that is popular because of its delicious, soft, and chewy characteristics, both in young and old seed processing. The obstacle that often arises in increasing production in the field is the availability of nitrogen-containing fertilizers such as urea, which are often rare and expensive. Reducing the nitrogen dose is attempted by only relying on NPK base fertilizer. The provision of a minimum dose of NPK base fertilizer (200 kg/ha) was studied in this study. The purpose of this study was to analyze the effect of nitrogen adequacy doses on the growth and production of waxy corn plants. This research was conducted at the Greenhouse of the Faculty of Agriculture, UMI Makassar, South Sulawesi Province. This research was designed in the form of a 2-factor factorial Randomized Block Design. Factor I consisted of Putra Baru 1, Putra Baru 2, and Arumba varieties, and factor II was urea fertilization at a dose of 100 kg/ha and without urea (control). Observations of growth and production components were observed when the plants were 100 HST old. The results showed that plant height and cob diameter had no significant effect. The weight of cobs per plant of the Putra Baru 1 and Putra Baru 2 varieties is higher than that of the Arumba variety. Urea fertilization of 100 kg/ha has a good effect on cob weight. There is no interaction between varieties and urea fertilization. An additional dose of 100 kg/ha of urea is needed if using a minimum NPK base fertilizer (200 kg/ha) to increase production